Secretory leukocyte protease inhibitor (slpi) expression downregulates E-cadherin, induces β-catenin re-localization and triggers apoptosis-related events in breast cancer cells - Rosso, Marina (2014)
BACKGROUND INFORMATION: Epithelial cadherin (E-cadherin) is involved in cell–cell adhesion through its extracellular domain, whereas the intracellular domain interacts with adaptor proteins, i.e. β-catenin, links E-cadherin to the actin cytoskeleton and participates in signal transduction events. E-cadherin protects mammary epithelial cells from apoptosis and its loss during tumour progression has been documented. Secretory Leukocyte Protease Inhibitor (SLPI) has anti- and pro-tumourigenic activities but its role in breast cancer has not been fully elucidated. Notwithstanding its relevance, how SLPI affects E-cadherin in breast cancer is still unknown. This study evaluated the effect of SLPI upon E-cadherin/β-catenin expression and apoptosis-related markers in murine (F3II) and human (MCF-7) breast tumour cells either treated with exogenous recombinant human SLPI (rhSLPI) or stably transfected with a plasmid encoding its sequence. RESULTS: Addition of rhSLPI to F3II cells caused a decrease (P < 0.05) in E-cadherin transcript and protein levels. Similar results were observed in SLPI-stable F3II transfectants (2C1), and treatment of 2C1 cells with a siRNA toward SLPI restored E-cadherin to control levels. SLPI-expressing cells showed disruption of E-cadherin/β-catenin complex and increased (P < 0.05) percentage of cells depicting nuclear β-catenin localisation. Associated to these changes, 2C1 cells showed increased Bax/Bcl-2 ratio and p21 protein levels, decreased c-Myc protein levels and decreased Cyclin D1 and Claudin-1 transcript levels. No differences in N- and P-cadherin were observed between SLPI-transfected cells and controls. Addition of rhSLPI to MCF-7 cells or stable transfection with SLPI caused a decrease (P < 0.05) in E-cadherin expression (transcript/protein) and its redistribution to the cytoplasm, as well as β-catenin re-localisation to the cell nucleus. CONCLUSIONS: Expression of SLPI was associated to a decrease in E-cadherin expression and re-localisation of E-cadherin to the cell cytoplasm and β-catenin to the cell cytoplasm and nucleus, and had pro-apoptotic and cell cycle-arrest effects.